Pemanfaatan Teknik Simpul untuk Pembuatan Tas Berbahan Denim - Ramawati, Deni; Josef, Adji Isworo (Institut Seni Indoensia Surakarta, 2022)
Denim is one of the oldest materials in the world, and until now the material is still known to everyone. The use of denim fabric for textile products is a phenomenon that will never die from time to time because this material is always used in creating a fashion product. Bags are one of the things that can support the appearance made of various textile materials, one of which is denim. The use of the knot technique in the manufacture of women's bags aims to provide a new alternative in making bags without sewing techniques. The knot technique is able to provide its own value in a work even if only by using a simple knot. The result of the design is a denim bag tote bag and a drawstring sling with a knot technique. Using the design method according to SP Gustami which consists of three stages, namely exploration, design, and realization.Keywords: denim, knots, woman’s bag.